Diffuse midline glioma in the spinal cord with rapid respiratory deterioration. Issue 1 (13th March 2020) - Kamidani, Ryo; Okada, Hideshi; Yasuda, Ryu; Yoshida, Takahiro; Kusuzawa, Keigo; Ichihashi, Masahiro; Kakino, Yoshinori; Oiwa, Hideaki; Kitagawa, Yuichiro; Fukuta, Tetsuya; Suzuki, Kodai; Okamoto, Haruka; et al.
Abstract : Background: Neurogenic acute respiratory failure is usually caused by either infection or vascular insufficiency. We report the case of a patient who developed acute respiratory failure secondary to a spinal tumor. Case Presentation: A 32‐year‐old man, presenting with numbness and muscle weakness in his legs for 2 weeks, was transferred to our hospital with worsening quadriplegia and development of respiratory symptoms. We carried out emergent spinal decompression and initiated steroid pulse therapy, with no resolution of symptoms; a tumor incision biopsy after contrast cervical magnetic resonance imaging revealed an intraspinal tumor with a pathological diagnosis of World Health Organization grade IV glioma. The patient developed bradycardia, severe sepsis, status epilepticus, and cardiopulmonary arrest due to hypoxemia and was treated with chemoradiotherapy under mechanical ventilation. He was later transferred to another hospital for subacute care. Conclusion: Acute respiratory failure caused by spinal tumors is uncommon. However, acute care practitioners should be mindful of neoplastic lesions as a potential cause. Abstract : Neurogenic acute respiratory failure caused by spinal tumors is uncommon. However, acute care practitioners should be mindful of neoplastic lesions as a potential cause.